The association between artificial light at night and prostate cancer in Gwangju City and South Jeolla Province of South Korea. (7th February 2017) - Kim, Ka Young; Lee, Eunil; Kim, Yun Jeong; Kim, Jinsun
ABSRACT: Exposure to artificial light at night (ALAN) has been reported to be associated with various pathological changes including sleep deprivation, circadian rhythm disruption, and melatonin suppression with increase in various cancers such as breast or prostate cancers. In this study, we sought to elucidate the association between ALAN and prostate cancer in 27 districts within Gwangju City and urban and rural areas from South Jeolla Province in South Korea. We analyzed the correlation between ALAN and the incidence of a range of cancers by Poisson regression analysis, after adjustment for confounding risk factors, such as smoking, drinking, obesity, stress, air pollution (particulate matter <10 μm in diameter), urbanization (proportion of urbanized area), and the cancer screening rate. Interestingly, the incidence of prostate cancer was significantly associated with ALAN (risk ratio = 1.02, p = 0.0369) and urbanization (risk ratio = 1.06, p = 0.0055). In particular, comparing the prostate cancer incidence at 25% and 75% level of ALAN, the risk ratio was 1.726 (12.6 over 7.3, respectively). No significant association was observed between ALAN and other cancers, including stomach, esophageal, liver, pancreatic, laryngeal, lung and tracheal, bladder, and brain and central nervous system cancers, as well as lymphoma and multiple myeloma. In conclusion, this study shows that a high incidence of prostate cancer may be independently associated with light pollution and urbanization, which represent significant factors in the rapid process of industrialization of South Korea.